A Review Study on Medicinal Uses and Health Advantage of Chili Pepper (International Journal of Innovative Research in Computer Science & Technology, 2021)
Eritrea has traditionally farmed and utilized  pepper, but it is an important element of the Eritrean culinary  culture. Eritrean pepper germplasm has been revealed to be  quite varied, with the ability to serve a wide range of  applications and purposes. Pepper is well-known over the  globe for its great nutritional value, health advantages, and  therapeutic characteristics. It contains a lot of vitamins and  minerals, as well as antibacterial and cancer-fighting  capabilities. Chili pepper offers anti-cancer, anti therapeutic, anti-inflammatory, including antiinflammatory qualities for rheumatism, bronchitis stiff  joints, or chest infections with cough as well as headache,  arthritis, cardiac arrhythmias, and a range of other diseases.  Even though medicinal plants are employed in Eritrea's  conventional healers, there is no proof that pepper was ever  utilized as a medicinal plant. The purpose of this review was  to raise awareness about the medicinal uses but also  therapeutic properties of this well-known but also widely  consumed power station to encourage studies into issues  including such quality, safety, efficacy, as well as growth, or  to prevent possible risks, especially those relating to  aflatoxin contamination.
Keywords: Aflatoxin; Chili Pepper; Capsaicin; Health Risks; Medicinal Use